Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

You can ask your own question or look at similar Maths questions.

5=(4/3) +x

x =(15-4)/3

x= 11/3

5 = 4/3 + x

Hence X=5-4/3

i.e X=11/3 Ans.

5 = 4/3 + x

Now we multiply the entire equation by 3 to remove the denominator

Therefore :- 15 = 4 +3x       ( 4/3 x 3 = 4)

- 15-4 = 3x

- 11 = 3x

x= 11/3

Step 1:  Multiply 5 by (3 + x) to eliminate the fraction:

Step 2: Set up the equation  15 +  5x = 4

Step 3:  Subtract 15 from both sides so 5x = -11

Step 4:  Divide both sides by 5 so x = -11 / 5 = - 2.2

5=(4/3)+x

5-(4/3)=x

x=3.67

Oh sorry. I thought that (3+x) was all in the numerator.

so its : 5=4/3 +x

so we move the 4/3 on the other side of the equation:

5-4/3=x

taking least common factor we get ((5*3)-4)/3=x

giving 11/3=x

The first step is to carefully observe the question. Sometimes observing makes it a lot more easier.

In the question 3+x the numerator is multiplied on both sides making 5*(3+x)=4

next open the bracket: 15+5x=4

now take 15 to the other side: 5x=4-15

5x=-11 so

x=-11/5

5=4/3+x

5-4/3=x

4/3=1and 1/3

remember, 3/3=1

hence, 5-1 1/3=5-1 and (3/3-1-3)

1. 5=(4)/(3)+x
2. x+(4/3)=5            Rewrite it to have the x on the left hand side to make it a little easier to see the steps
3. x=5-(4/3)             Take the 4/3 away from both sides of the expression
4. x=(15/3)-(4/3)      Since 5=15/3 we can write it like this
5. x=(15-4)/3            Rearrange again to have the expression over one denominator
6. x=11/3                  15-4=11 so therefore the numerator is 11
7. x=11/3; or x=3 and 2/3; or x=3.6666 (repeating indefinitely)

11/3 is definitely the correct answer.

5=(4/3)+x

5-(4/3)=x

(15-4)/3=x

11/3=x

3.666666667=x

Dear cyndrachoo.

You'd be well served to ignore Holly's answer. It's plainly wrong. The answer is 11/3 (or 3 and 2/3) as explained by vishal.

The easiest way to simplify your fraction is to swap it over so that you are dealing with numbers on one side. In this equation, the brackets signify that they are part of a fraction so (4)/(3) is four thirds. Remember that in fractions, a the integer (whole number) 3 can be represented as (3)/(1):

5 = (4)/(3)+x

x = (4)/(3) + (5)/(1)       swap the equation around to allow us to work with numbers

x = (4)/(3) + (15)/(3)    next multiply the 2nd fraction so the denominators are the same

x = (19)/(3)                  We now have a single fraction, but can go further

19 /3 = 6 r1                  because the numerator is bigger, divide them to get the integer

x = 6 + (1)/(3)              simplified